Reexamining the Conditional Effect of Foreign Direct Investment - Randolph Bruno; Nauro F. Campos (Institute for the Study of Labor (IZA), 2013)
The prevailing consensus is that foreign direct investment (FDI) effects are conditional. At the macro level, they depend upon minimum levels of human capital or financial development, while at the micro level, they depend on type of linkage (forwards, backwards, or horizontal). This paper presents new evidence showing that these effects are substantially less conditional. We use a meta-analysis on two data sets covering 549 micro and 553 macro estimates of the effects of FDI on performance. We find these effects tend to be larger in macro than in micro studies, and greater in low- than in high-income countries.
Keywords: C83; F23; O12; 330; foreign direct investment; economic growth; firm performance; meta-regression-analysis